Sruti and Apauruseya : An Approach to Religious Scriptures and Revelation - Purushottama Bilimoria (Journal of Dharma, 2020)
This article is part of a larger project on the problem of how word can be a means of knowing, which is popularly known as the thesis of sabda-pramana in Indian philosophy, and which has not hitherto received the systematic treatment that I have attempted in my work. The question, while being put philosophically, is not without its bearing in the context of religion and religious studies, especially as regards the status and sanction given to religious scriptures and to revelation in almost any tradition.